Genetic Analysis for Two Italian Siblings with Usher Syndrome and Schizophrenia - Daniela Domanico; Serena Fragiotta; Paolo Trabucco; Marcella Nebbioso; Enzo Maria Vingolo (Case Reports in Ophthalmological Medicine)
Usher syndrome is a group of autosomal recessive genetic disorders characterized by deafness, retinitis pigmentosa, and sometimes vestibular areflexia. The relationship between Usher syndrome and mental disorders, most commonly a “schizophrenia-like” psychosis, is sometimes described in the literature. The etiology of psychiatric expression of Usher syndrome is still unclear. We reported a case of two natural siblings with congenital hypoacusis, retinitis pigmentosa, and psychiatric symptoms. Clinical features and genetic analysis were also reported. We analyzed possible causes to explain the high prevalence of psychiatric manifestations in Usher syndrome: genetic factors, brain damage, and “stress-related” hypothesis.